Prevalence of food insecurity and its association with depressive and anxiety symptoms in older adults during the COVID-19 pandemic in Mexico: A secondary analysis of ENCOVID-19 survey - Alán, De la Vega Martínez; Oscar, Rosas-Carrasco; Pablo, Gaitán-Rossi; Mónica, Ancira-Moreno; Miriam, López-Teros (Frontiers in Medicine, 2023)
Introduction: COVID-19 infection has caused high rates of morbi-mortality in older adults (OA). Besides, conditions such as depression, anxiety, unemployment and poverty frequently contribute to this population being at higher risk of food insecurity (FI) during COVID-19 pandemic. Objective: To analyze the prevalence of FI and its association with depressive and anxiety symptoms in Mexican OA during the COVID-19 pandemic. Methods: Secondary analysis of the National Survey on the Effects of COVID-19 on the Well-being of Mexican Households (ENCOVID-19); a series of cross-sectional telephone surveys between April and October 2020, the OA subsample was 1,065. FI was measured by using the Latin American and Caribbean Food Security Scale (ELCSA), depression and anxiet symptoms with the Depression Scale of the Center for Epidemiological Studies (CESD-7) and the Generalized Anxiety Disorder Scale (GAD-2), respectively. Socioeconomic status (SES), occupation, schooling and pension were also evaluated. ANOVA was used to compare the variables between the different FI groups and logistic regression was used to analyze the risk between FI and the anxiety and depression variables. Results: Mean age of 67.31 ± 6.4 years, FI was classified as mild, moderate and severe with prevalence’s of 38.6%, 15.04% and 8.16%, respectively. 28.01% of the OA presented symptoms of anxiety and 39.09% of depression. In the comparison between groups, higher prevalence’s of depressive symptoms were observed with a higher degree of FI, 65.75% in severe-moderate, 10.39% in mild and 9.40% without FI, p≤0.000. Regarding anxiety symptoms, 48% showed moderate and severe, 30.05% in mild and 15.38% without FI, p≤0.000. Using multiple logistic regression, an OR=5.50 (95% CI 2.74-11.04) was observed for depressive symptoms when moderate-severe FI is present. In the case of the risk of anxiety symptoms, it was significant in all degrees of FI, in mild (OR=2.43, 95% CI 1.66-3.59) and in moderate and severe ( OR=5.32, 95% CI 3.45-8.19). Conclusions: There is a high prevalence of FI in Mexican OA during the COVID-19 pandemic. FI increases the risk of other conditions such as depression and anxiety. Its important to design programs aimed at OA with these conditions to reduce or prevent FI.